Kepentingan Taiwan Menginisiasi Normalisasi Hubungan dengan Cina Pasca Krisis Taiwan Tahun 2000-2004 - Pryamedha Artha, Kadek Kara; Priadarsinirainypriadarsini@unud.ac.id, Ni Wayan Rainy; Intan Prameswari, Anak Agung Ayu (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2018)
ABSTRACT Taiwan Strait crises started when China conducted missiles trials near Taiwan sea on 1995-1996. China used missile trials as a form of deterrence to end Taiwan independent movement. The missile trials ended in 1996, however China established another deterrence move by preparing military army facing to Taiwan border. This is the main cause of Taiwan insecurity after the end of crises. Disparity military power between Taiwan and China has made Taiwan more insecure. This circumstance described on asymmetrical relations theory which explains that weak states tend to feel dilemma and paranoid when strong state takes an action because strong states has the capability to control situation. As a response, Taiwan had to initiate normalization with China to stabilize situation. Although for 50 years long, Taiwan had confidence for not making a contact with China. But Taiwan urgently needs to protect their national interest by initiating normalization. Keywords: Taiwan Strait crises, asymmetrical relations, normalization initiation, national interest.